Frae ither tongues : essays on modern translations into Scots - Findlay, Bill, 1947- (Topics in translation, 2004)
The period since the 1930s has been the richest for literary translation into Scots since the 16th century. This collection of essays, by translators and critics, represents an extended analysis of the nature and practice of modern translation into Scots.